Performace Measurement of Intellectual Capital - Grigoryan, Ani; Sabolovič, Mojmír, 1978-; Dvořák, Jiří; Vysoká škola ekonomická v Praze. Fakulta managementu (2023)
The aim of this thesis is to review the existing measurement methods of intellectual capital and assess the effect intellectual capital has on a firm’s financial performance. It is structured into theoretical and practical sections. The theoretical part includes an extensive literature review on intellectual capital types and measurement methods. The practical part presents a statistical analysis, determining how intellectual capital influences a company’s financial performance. This analysis utilizes five years of data from 880 firms across various sectors and countries. The findings indicate a positive correlation between certain intellectual capital components and financial performance, with industry-specific differences observed.
Vedoucí práce: Mojmír Sabolovič
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta managementu, 2024
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2024
Způsob přístupu: Internet
Keywords: management [obor dipl. práce]; diplomové práce; master's theses